2021
DOI: 10.3390/pathogens10050565
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Immunological Factors Influencing Pathogenesis in Patients with COVID-19: A Review on Viral Dissemination, Immunotherapeutic Options to Counter Cytokine Storm and Inflammatory Responses

Abstract: The pathogenesis of coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is still not fully unraveled. Though preventive vaccines and treatment methods are out on the market, a specific cure for the disease has not been discovered. Recent investigations and research studies primarily focus on the immunopathology of the disease. A healthy immune system responds immediately after viral entry, causing immediate viral annihilation and recovery. However, an im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 252 publications
1
54
0
Order By: Relevance
“…This might be attributed mainly to the differences in the inclusion criteria and the population age groups included in the studies, or it could be explained by the gender-based biological differences in the host immune response to COVID-19 infection [ 102 ]. The age-dependent defects in T-cell and B-cell function and the excess production of type 2 cytokines could lead to a deficiency in control of viral replication and more prolonged proinflammatory responses, potentially leading to poorer outcomes [ 103 ]. Yet, SARS-CoV-2 patients of any age may develop such coinfections and experience severe disease, especially in those with comorbidities, even in young people [ 4 , 53 ], children [ 27 , 49 ], and infants [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…This might be attributed mainly to the differences in the inclusion criteria and the population age groups included in the studies, or it could be explained by the gender-based biological differences in the host immune response to COVID-19 infection [ 102 ]. The age-dependent defects in T-cell and B-cell function and the excess production of type 2 cytokines could lead to a deficiency in control of viral replication and more prolonged proinflammatory responses, potentially leading to poorer outcomes [ 103 ]. Yet, SARS-CoV-2 patients of any age may develop such coinfections and experience severe disease, especially in those with comorbidities, even in young people [ 4 , 53 ], children [ 27 , 49 ], and infants [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown the relation between haematologic, inflammatory and coagulation parameters with the severity of the disease [ 20 , 21 , 22 , 23 , 24 ], although only a limited number of studies examine the effect of pro-fibrotic and OS markers on the severe clinical course of COVID-19 patients. In this study we analysed, for the first time, the potential value of haematologic, inflammatory and coagulation parameters, together with pro-fibrotic and OS markers as prognostic biomarkers for ARDS development in COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the ROC analysis showed that the ability of the AUC of IL-6 to predict disease severity was one of the highest, demonstrating its predictive power for the severity of COVID-19 patients over the course of hospitalisation. In fact, determining the IL-6 level, together with TNF-α, could be considered as a clinical tool for stratifying high-risk patients, and identifying those who should be treated with the IL-6R antagonist tocilizumab [ 21 , 22 , 23 , 24 , 27 , 28 , 29 ]. IL-7, a cytokine with a similar signal transduction pathway to IL-6, may be considered a prognostic marker [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…27 The elevated levels of cytokine or hypercytokinemia leads to ARDS along with multiple organ damage. 28 Although an article had corroborated the advantage of using prednisone in COVID-19 patients, 19 utilizing high-dose corticosteroids in critically ill patients is complicated and must be used with extreme care to avoid aggravating complications by worsening laboratory parameters and risk of death. 29,30 Our findings revealed that AKI was an indicator of severe infection and death (OR (95% CI): 7.279 (1.191-65.43), p = 0.032).…”
Section: Discussionmentioning
confidence: 99%